Clarke's analytical forensic toxicology - Negrusz, Adam; Cooper, Gail AA (Pharmaceutical Press, 2013)
This second edition of Clarke's Analytical Forensic Toxicology offers a fresh perspective on the drugs and poisons that you are most likely to encounter in forensic toxicology, with a focus on collection, extraction and analysis